Implants for surgery - metallic materials-classification of microstructures for alpha+beta titanium alloy bars (ISO 20160:2006, IDT) - Abdul Razak, Noor Hayati; Yaakop, Salbiah; Choon, David; Goonting, Tracy E.; T, Mahadevan; Law, Ching Yee; How, Kim Chuan; Singh, Harwant; Ismail, Zulkharnain; Manickam, Thirumal; Yaakob, Mohd Amin; Mohd Yusof, Hyzan; et al. (SIRIM Berhad, 2011)
This Malaysian Standard provides a catalogue of metallographic photomicrographs for the designation of microstructures of alpha+beta titanium alloys in the form of bars that are intended for the manufacture of surgical implants. This Malaysian Standard is applicable to bars of diameter no greater than 100 mm or the equivalent. This catalogue of microstructures is intended to serve as an aid in the communication on general types of microstructures of alpha+beta titanium alloy bars. The designation of the microstructures is based on morphological appearance. Actual microstructures can also appear as a combination of the type of micrographs shown. ?This Malaysian Standard does not contain specific microstructural requirements. The catalogue includes photomicrographs of desirable and undesirable microstructures that can develop during the processing of alpha+beta titanium alloys. The selection of acceptable microstructures is subject to agreement under the consideration of implant app